2009
DOI: 10.1128/aac.00812-08
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationships of Antimicrobial and Lipoteichoic Acid-Sequestering Properties in Polyamine Sulfonamides

Abstract: We have recently confirmed that lipoteichoic acid (LTA), a major constituent of the gram-positive bacterial surface, is the endotoxin of gram-positive bacteria that induces proinflammatory molecules in a Toll-like receptor 2 (TLR2)-dependent manner. LTA is an anionic amphipath whose physicochemical properties are similar to those of lipopolysaccharide (LPS), which is found on the outer leaflet of the outer membranes of gram-negative organisms. Hypothesizing that compounds that sequester LPS could also bind to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…For instance, antibodies to LTA are currently being investigated as a basis for the treatment of infections with Grϩ bacteria (61). Others have proposed sulfonylamide compounds as therapeutic agents, since sulfonylamide may selectively inactivate LTA without inactivating lipoproteins (59). These new approaches may be less fruitful if LTA is not critically involved in infections with Grϩ bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, antibodies to LTA are currently being investigated as a basis for the treatment of infections with Grϩ bacteria (61). Others have proposed sulfonylamide compounds as therapeutic agents, since sulfonylamide may selectively inactivate LTA without inactivating lipoproteins (59). These new approaches may be less fruitful if LTA is not critically involved in infections with Grϩ bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that these compounds indeed bind and neutralize LTA, as reflected by the inhibition of TLR2-mediated NF-κB induction in reporter gene assays. Structure-activity studies showed a clear dependence of the acyl chain length on activity against LTA in compounds with spermine and homospermine scaffolds [54]. We then sought to examine possible correlations between the neutralizing potency toward LTA and antimicrobial activity in S. aureus.…”
Section: Neutralization Of Endotoxin By Lipopolyaminesmentioning
confidence: 99%
“…Many sulfa drugs containing SO 2 NH moiety assume an active role in chemotherapeutic field such as sulfonamides, sulphathiazole and sulphamerazine [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%